Penanaman Nilai Karakter sebagai Upaya Mereduksi Dampak Negatif Era Digital - Syur’aini Syur’aini; Setiawati Setiawati; Vevi Sunarti (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
Today we have been in the digital era, but many people are not aware of it so that errors often occur in the use of digital devices. Everywhere can be witnessed the fun of playing gaged especially for the younger generation and students so that the time is spent on playing online games. Actually, there are many advantages that can be gained in this era, but the weakness is far more and dangerous if it is not regulated in its use. For this reason, a solution is needed in the form of teacher collaboration with parents in educating children. Keyword; digital era, character